A few days ago

# how would i solve for x?

y(x+3)=2x-1

Top 4 Answers

A few days ago

Favorite Answer

yx + 3y =2x -1

3y +1 =2x -yx

3y +1 = x(2-y)

3y +1 = x

——-

2-y

1

A few days ago

y(x+3) =2x – 1

yx + 3y= 2x -1

yx + 3y +1+2x

3y + 1 = 2x – yx

3y + 1 = x – y

add y to both sides

4y +1 = x

0

A few days ago

y(x+3)=2x-1

now multiply y as a common term to x and 3

yx+3y=2x-1

take -1 on the other side it becomes +1 (signs change)

yx+3y+1=2x

similarly take yx on other side

3y+1=2x-yx

x is common on R.H.S (right hand side)

3y+1=x(2-y)

again sign changes

thus,

x=3y+1/2-y (ANSWER)

0

A few days ago

xy + 3y = 2x – 1

xy + 3y -2x = -1

xy – 2x = -1 – 3y

x(y-2) = – 1 – 3y

x = (-1-3y)/(y-2)

0

- Academic Writing
- Accounting
- Anthropology
- Article
- Blog
- Business
- Career
- Case Study
- Critical Thinking
- Culture
- Dissertation
- Education
- Education Questions
- Essay Tips
- Essay Writing
- Finance
- Free Essay Samples
- Free Essay Templates
- Free Essay Topics
- Health
- History
- Human Resources
- Law
- Literature
- Management
- Marketing
- Nursing
- other
- Politics
- Problem Solving
- Psychology
- Report
- Research Paper
- Review Writing
- Social Issues
- Speech Writing
- Term Paper
- Thesis Writing
- Writing Styles